Differences in visio-spatial intelligence between non-athletes and netball players - Mathe, Nonkululeko; Millard, Lourens; Breukelman, Gerrit Jan; Mathunjwa, Musa (Frontiers in Sports and Active Living, 2023)
There is conflicting evidence regarding whether athletes have better visio-spatial skills than non-athletes. This gap may result from athletes' superiority in only some visio-spatial abilities (VSS), rather than all areas of vision. The aim of this study was to determine whether there is a significant difference in the visio-spatial intelligence between female netball players (n = 40) and non-athletes (n = 40) when comparing six visual skills (accommodation facility, saccadic eye movement, speed of recognition, peripheral awareness, hand-eye coordination, and visual memory). Following an optometric evaluation, the participants were assessed in six distinct established tests, including the hart near far rock, saccadic eye movement, evasion, accumulator, ball wall toss tests, and flash memory, to evaluate the VSS components of non-athletes and premier league netball players. For five of the six tests, there was a statistically significant (p ≤ 0.05) difference between netball players and non-athletes. Conversely, there is no concrete evidence that netball players have better visual memory than non-athletes (p = 0.277). When compared to non-athletes, netball players have significantly improved accommodation facility (p < .001), saccadic eye movements (p < .001), speed of recognition (p < .001), peripheral awareness (p < .001), and hand-eye coordination (p < .001), but not visual memory (p = 0.277). The findings that netball players perform better on a certain VSS have broad ramifications for theories of sport vision, the optimal way to choose tests, and the creation of VSS testing batteries for specific sports.